2016
DOI: 10.1177/1457496916665763
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Fistula-in-ano Among Patients With Crohn’s Disease: Analysis of Outcomes After Fistulotomy or Seton Placement—Single-Center Experience

Abstract: Fistulotomy could achieve good results in terms of wound healing and incontinence in strictly selected patients with Crohn's disease suffering from low-lying transsphincteric fistulae. For more high-lying or complicated fistulae, seton placement is more appropriate. For high transsphincteric fistulae, the only option is placement of loose seton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
(35 reference statements)
1
6
0
1
Order By: Relevance
“…This risk is comparable in the short and long terms. These data are in line with previous reports [18,19]. Some words of caution are needed.…”
Section: Discussionsupporting
confidence: 92%
“…This risk is comparable in the short and long terms. These data are in line with previous reports [18,19]. Some words of caution are needed.…”
Section: Discussionsupporting
confidence: 92%
“…Few reports of CD patients treated with DDS have been published. [7][8][9][10][11][12][13][14][15] Although all have consistently highlighted the safety of DDS in regards to effects on anal sphincter control, short-term success rates vary from 59% to 100% with longer follow-up revealing a high (35%-44%) incidence of recurrent sepsis. [7][8][9][10][11][12] Our data are consistent with these reported long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there have been few modern reports on the use of DDS in CD, possibly reflecting the effectiveness of biologic therapy in promoting fistula healing and the use of new surgical treatments such as LIFT which have been reported to be safe in CD patients with anal stenosis, active proctitis, or anal canal ulceration. 3,4,[13][14][15] It is interesting to speculate that the reported effectiveness of stem cell therapy for these fistulas 5 might continue to reduce the need for DDS in CD. Defining clinical variables that predict outcomes of DDS in CD is important both for patient prognostication and guiding surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…In a case series led by Kelly et al, 7% (14/200) had spontaneous resolution of the fistula tract with seton placement alone [1]. The study by Papaconstantinou et al reported improvement in all 25 cases of mid-or low-level trans-sphincteric fistula in CD, with recurrence six months after seton removal in one patient, and minor incontinence was found in 12% (3/25) [26]. Incontinence rates associated with loose setons have been significantly lower, varied from 5-17%, compared to cutting setons [27,28].…”
Section: Seton Placementmentioning
confidence: 99%